Successful development of molecular diagnostic technology combining mini-barcoding and high-resolution melting for traditional Chinese medicine agarwood species based on single-nucleotide polymorphism in the chloroplast genome - Feng, Jian; Liu, Yangyang; Xie, Anzhen; Yang, Yun; Lv, Feifei; Wei, Jianhe (Frontiers in Plant Science, 2024)
Agarwood is a valuable traditional medicine and fragrance. The production process is a typical injury-induced defense response. Currently, there are approximately 22 known species in the genus Aquilaria Lam., all of which can produce agarwood, while there are only two legal species of traditional Chinese medicinal agarwood, Aquilaria sinensis (Lour.) Spreng. and Aquilaria agallocha (Lour.) Roxb. The Taiwan herbal Pharmacopoeia of China stipulates that the medicinal agarwood species are A. sinensis and its relatives in the same genus. Moreover, there are five species of agarwood available for clinical medicinal use in Japan, including A. agallocha and A. sinensis, which are often confused with each other or used in a mixed way in the trade process. Therefore, accurate identification of traditional Chinese medicinal agarwood species is important to ensure the authenticity of traditional medicines and to guide the safety of clinical medication. In this study, 59 specific single-nucleotide polymorphism loci were screened and obtained from the chloroplast genomes of 12 species of the genus Aquilaria Lam. We established an identification method for traditional Chinese medicinal agarwood using mini-barcoding combined with high-resolution melting (HRM) and designed and validated ten pairs of primers from the psbM-trnD, psbA, rps16, petN, ndhE-psaC, rps4, atpE, ycf1, rps15-trnN, and matK regions. The amplification products were all less than 200 bp, with a high success rate of amplification. The method was applied to successfully identify traditional Chinese medicinal agarwood species from commercial agarwood samples.Overall, the sensitivity of this method was sufficient to detect 1% of adulterants in medicinal agarwood products, proving that mini-barcoding HRM is a powerful and flexible tool. This method can be used as a fast and effective high-throughput method for authenticity testing of traditional Chinese medicinal agarwood and its raw materials containing agarwood-containing proprietary Chinese medicines and is recommended for industrial applications.